Debriefing to improve outcomes from critical illness: a systematic review and meta-analysis - Couper, K.; Salman, B.; Soar, J.; Finn, Judith; Perkins, G. (Springer-Verlag, 2013)
Purpose: Intensive care clinicians play a central role in the coordination and treatment of patients that develop life-threatening emergencies. This review evaluates the effect of debriefing after life-threatening emergencies and considers the implications for intensive care training and practice. Methods: Studies were identified by searching electronic databases, citation tracking, and contact with subject specialists. Studies evaluating the effect of debriefing after life-threatening emergencies on clinician performance (process) and/or patient outcomes were eligible for inclusion. Study quality was assessed and summarised using the GRADE system. Results: The search identified 2,720 studies. After detailed review, 27 studies were included of which 20 supported the use of debriefing. Debriefing was viewed positively (n = 3), improved learning (n = 1), enhanced non-technical performance (n = 4) and technical performance (n = 16), and improved patient outcomes (n = 2).Four cardiac arrest studies were suitable for meta-analysis. This found evidence of improved resuscitation process outcomes [compression fraction (mean difference 6.80, 95 % CI4.19–9.40, p\0.001)] and short-term patient outcome [return of spontaneous circulation (OR 1.46,95 % CI 1.01–2.13, p = 0.05)].There was no effect on survival to hospital discharge (OR 0.80, 95 % CI0.38–1.67, p = 0.55). Conclusions: This review supports the use of structured debriefing as an educational strategy to improve clinician knowledge and skill acquisition and implementation of those skills in practice. However, the effect of debriefing on long-term patient outcomes is uncertain. There remains a need for further high-quality research, which seeks to identify the optimal method for debriefing delivery and effect on patient outcomes.